Book Design of Online-Based Islamic Education Subjects At the Universitas Nahdlatul Ulama Blitar - Siti Uswatun Kasanah; M. Subhan Ansori; Abd. Charis Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
Reference books on Islamic Religious Education (PAI) courses in General Higher Education (PTU) need to be designed in line with the Industrial Revolution 4.0 era. This paper is to make a reference book for Islamic Religious Education courses in General Higher Education and to design reference books online. The focus of this research is the development of Islamic religious education reference books in online-based Public Higher Education. Using the Research and Development method developed by Dick and Carey. The data was collected from the assessment of two experts through the Expert validation sheet and 11 MKDU Lecturers through the respondent questionnaire. Data analysis uses qualitative and quantitative approaches. Data analysis that Islamic Education courses at the Blitar University of Nahdlatul Ulama need to be made references and designed online. The results showed that the reference book was appropriate to be used as a reference in Islamic Religious Education courses. This is based on material validation of 410 (very good), language and images of 401 (very good), presentation of 691 (very good), display of 252 (very good).